Adipocyte PHLPP2 inhibition prevents obesity-induced fatty liver - KyeongJin Kim (Nature Portfolio, 2021)
Obesity can be associated with an increased risk of metabolic complications. Here, the authors show that adipocyte-specific ablation of the phosphatase PHLPP2 improves glucose homeostasis in high-fat diet fed obese mice, and that this may be due at least in part to PHLPP2 dephosphorylation of HSL.